NILAI STRATEGIES USAHA JASA TEMPAT KOS BAGI MAHASISWA SEBAGAI EXTERNAL SUPPORT SYSTEM PADA KUALITAS KEHIDUPAN KAMPUS (QUALITY OF COLLEGE LIFE) - Andi Setiawan; Suwardi Suwardi; Khairul Saleh; Suharmanto Suharmanto (Politeknik Negeri Semarang, 2017)
Quality of College Life (QCL) is one of the performance measurement instruments of a highereducation institution. The results of the Tiyarattanachai and Hollmann studies (2016) warnedthat educational institutions always prioritize internal factors is something that is common, but itis not true if educational institutions ignore external factors. Both factors must be balanced for amaximum result. The results of direct observation of this research in the form of preliminarydata, where there are found 664 business boarding houses in the city of Semarang. It gives riseto social, cultural, security and competition for the business of Kos-boarding houses andconsumers in this case students. The formulation of this research problem is how the strategicvalue of business services boarding houses / boarding houses for students as an external supportsystem on the quality of life of the campus with structural model analysis approach. The plan ofresearch needs from the beginning to the end is 5 (five) months. Sampling technique used in thisresearch is accidental sampling method in this case that is students who use business servicesboarding houses / boarding houses in the city of Semarang. For the sample size is 100 for SEManalysis tools with AMOS 22.00. In addition to SEM, this study also performs reliability test,validity test, decryption index analysis test, and others. In the end it is expected that this researchcan answer will be partially and simultaneously influence the value of environmental life,competitive economic value, and strategic location value to student achievement behavior,through the quality of campus life.